PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA TANGERANG SELATAN - Thamrin; Dwi Rizki, Cintia (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of Leadership Style and Physical Work Environment on Employee Performance at the South Tangerang City Education and Culture Service. This research uses the Associative Quantitative method where the data obtained is in the form of a questionnaire which is processed using the SPSS 26 application. The results of this research are that Leadership Style has a significant effect on Employee Performance at the South Tangerang City Education and Culture Service as shown by the regression equation Y = 20.444 + 0.249 X₁ and hypothesis testing obtained t_count>t_table or (5.729>1.978). The physical work environment has no effect on employee performance as shown by the regression equation Y = 20.444 + 0.249 Leadership Style and Physical Work Environment simultaneously have a significant effect on Employee Performance with the regression equation Y = 28.824 + 0.226 X1 - 0.243 X₂. The coefficient of determination value is 33.2% while the remaining is 66.8%. Hypothesis testing obtained a value of F_count>F_table or (31.996 > 3.070).